Implementation of the Corporate Social Responsibility Program in Strengthening SPMI Learning at Muhammadiyah 2 Vocational School, Pekanbaru - Hardhina Rosmasita; Moh. Mahfud Effendy; Dyah Worowirastri Ekowati (Journal of Creative Power and Ambition (JCPA), 2026)
The gap between the competencies of vocational education graduates and the needs of the business and industrial worlds demands collaboration that goes beyond social assistance. This article aims to describe the implementation of the Corporate Social Responsibility (CSR) program, analyze the impact/influence of CSR on the Internal Quality Assurance System (SPMI) of learning, and observe the changes that have occurred at SMK Muhammadiyah 2 Pekanbaru. The research used a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, documentation, and perception confirmation sheets as supporting data. The findings indicate that CSR is present through assistance with practical facilities, teacher training, guest teachers, internships/Prakerin, curriculum synchronization, certification support, teaching factories, and collaborative evaluations. The impact is seen in strengthening planning, learning implementation, practical facilities, evaluation, control, and quality improvement. However, this impact must be limited to qualitative impacts if the numerical data, UKK recap, portfolio, and evaluation documents are incomplete. This article concludes that CSR can be an instrument for strengthening SPMI if managed in a planned, measurable, documented, and sustainable manner.